Cerebellar Cortical Demyelination in the Murine Cuprizone Model - Skripuletz, Thomas (Brain Pathol, 2009)
In multiple sclerosis, demyelination occurs beside the white‐matter structures and in the cerebral and cerebellar cortex. We have previously shown that, in the cuprizone model, demyelination is present not only in the corpus callosum but also in the cerebral cortex. Here, we have performed a detailed analysis of the dynamics of de‐ and remyelination in the cerebellar cortex and white matter at nine timepoints in two cerebellar regions. To induce demyelination, C57BL/6 mice were fed with 0.2% cuprizone for 12 weeks followed by a recovery of 8 weeks. Both cortex and white‐matter structures were significantly demyelinated after 12 weeks of cuprizone feeding. Remyelination occurred after withdrawal of cuprizone but was less prominent in the more caudal cerebellar region. Microglia infiltration was prominent in all analyzed cerebellar areas, preceding demyelination by approximately 2–4 weeks, and was delayed in the more caudal cerebellar region. Astrogliosis was also seen but did not reach the extent observed in the cerebrum. In summary, cuprizone feeding provides an excellent model for the investigation of de‐ and remyelination processes in the cerebellar cortex and white matter. Furthermore, demyelination, microglia and astrocyte changes were different in the cerebellum as compared with the cerebrum, indicating region‐dependent pathomechanisms.